2004
DOI: 10.1177/1069072703257720
|View full text |Cite
|
Sign up to set email alerts
|

Motivational Correlates of Portuguese High Schoolers’ Vocational Identity: Cultural Validation of the Goal Instability Scale

Abstract: This study examined the relevance of the Goal Instability Scale-Portuguese Adaptation (GIS-P) on the vocational identity and career certainty of 375 10th-, 11th-, and 12th-grade Portuguese high schoolers. After translating the GIS-P, confirmatory factor analysis was used to examine the factorial unidimensionality and reliability of the construct. A multitrait-monomethod correlation matrix demonstrated convergent and divergent validity with personality, career, and social constructs. As expected, the GIS-P was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 39 publications
1
10
0
Order By: Relevance
“…Goal instability as a motivational personality construct reflecting the self's ability to organize itself through coherent and solid goals and to muster the energy to act on them [18]. This study of contingent employees in Taiwan semiconductor industry demonstrates that goal stability acts as a proxy for the self's ability to mobilize itself into career commitment.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Goal instability as a motivational personality construct reflecting the self's ability to organize itself through coherent and solid goals and to muster the energy to act on them [18]. This study of contingent employees in Taiwan semiconductor industry demonstrates that goal stability acts as a proxy for the self's ability to mobilize itself into career commitment.…”
Section: Discussionmentioning
confidence: 95%
“…Internal consistency is 0.81 [19]. Confirmatory factor analyses using diverse age groups have shown the GIS taps a unitary construct [18,24]. A six-point Likert-type scale ranging from "strongly disagree" to "strongly agree" is also adopted.…”
Section: B Measuresmentioning
confidence: 99%
See 1 more Smart Citation
“…For those measures for which establishing some sort of equivalence across different language versions was crucial, participants relied on the existing literature on methods that can assist test developers to approximate equivalence. These methods tend to comprise factor analytic techniques, especially confirmatory factor analysis (e.g., Ben Porath, 1990;Santos, Casillas, & Robbins, 2004), as well as analyses using item response theory, such as differential item functioning (e.g., Allalouf, Hambleton, & Sireci, 1999;Ellis, 1989;Ercikan, 2002).…”
Section: Validation Of Adapted Measurementioning
confidence: 99%
“…In this study, we used the Portuguese version of the GIS adapted by Santos, Casillas and Robbins (2004), with a sample of secondary school students. A confirmatory factor analysis indicated that the GIS assesses one single factor.…”
Section: Procedures and Instrumentsmentioning
confidence: 99%